CEO short‐term incentives and the agency cost of debt - Akins, Brian; Bitting, Jonathan; De Angelis, David; Gaulin, Maclean (Contemporary Accounting Research, 2025)
Abstract This paper shows that creditors' horizon interests impact the design of CEO compensation contracts. Using a regression discontinuity design, we find that borrowing firms provide shorter incentives to their CEO following a loan covenant violation. They do so by decreasing the horizon of pay and tilting the choice of performance metrics toward accounting goals, in particular short‐term ones. This effect is stronger when creditors' interests are more immediate, such as among loans with short remaining maturity and when borrowers have lower cash reserves. This effect is weaker when the cost to shareholders is higher, such as among firms with high growth opportunities. Together these results are consistent with boards intending to facilitate renegotiation and mitigate repayment risk while balancing shareholder interests. Overall, our evidence supports a novel reason for the use of short‐term incentives, namely to reduce the agency cost of debt.